1973
DOI: 10.1112/plms/s3-26.1.184
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Many-One Degrees by the Word Problem for Thue Systems

Abstract: The object of this paper is to show that, given any total recursive function g, one can effectively construct a Thue system T such that the decision problem for the range of g and the word problem for T are of the same many-one degree. It follows immediately that any many-one degree containing a recursively enumerable (r.e.) set can be represented by the word problem of some Thue system.The properties of Thue systems were investigated by Post ([4]), who was able to show that the general word problem is undecid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1975
1975
1981
1981

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…M. ZIEGLER [11] then showed that the result could not be extended to btt-degrees, even for recursively presented groups. I n contrast with ZIEGLER'S result, OVERBEEK [7] (extending earlier work of BOONE [2] for Turing degrees) showed that every r e . m-degree does contain the word problem of a finitely presented semigroup.…”
Section: Boone's Proof Is In [3 41 and References Tocontrasting
confidence: 45%
“…M. ZIEGLER [11] then showed that the result could not be extended to btt-degrees, even for recursively presented groups. I n contrast with ZIEGLER'S result, OVERBEEK [7] (extending earlier work of BOONE [2] for Turing degrees) showed that every r e . m-degree does contain the word problem of a finitely presented semigroup.…”
Section: Boone's Proof Is In [3 41 and References Tocontrasting
confidence: 45%
“…(I), (II), (III), (IV), and (V) were shown in [12], [7], [6], [9], and [8], respectively. (VI) and (VII) may be arrived at by combining the constructions of [3] with those of [7] and [9], respectively.…”
Section: Two-letter Alphabetsmentioning
confidence: 96%
“…More recent work has had as its objective the proof that these Turing degree results can be strengthened to many-one degrees. Examples of papers falling into this category are [6], [7], [8], [9], [10], and [12]. The constructions presented in each of the above lead to combinatorial systems in which the alphabets are finite but not uniformly bounded.…”
Section: Introductionmentioning
confidence: 97%
“…many-one degrees : the representation theorem for the decision problem of partial implicational propositional calculi in two variables (see HUGHES [36]), for the halting problem of Tag systems (AANDERAA, BELSNES [l]) with many-one equivalent word and halting probleni (HUGHES [32]), for the Post correspondence problem of correspondence classes resp. with arioni (CUDIA, SINGLETARY [16], HUGHES, SINGLETARY [39, chapter XI), for the word probleiri of Thue systems (OVERBEEK [53]), for the decision problem of recursive classes of first-order logical formulae with equality as only predicate symbol; the triple repraenfation theorem for halting, word and confluence problem of Turing machines (OVER-BEEK i52]), iMarkov algorithms without concluding rules (HUGHES [30]), Xarkov algorithms in Swanson…”
Section: %(Ptm)mentioning
confidence: 99%
“…Following BOONE'S suggestion prompted by this former work1) that such equivalence theorems might hold for stronger notions of degree reducibility, HUGHES, OVERBEEK, SINGLETARY [37] generalized tthe results of SINGLETARY I661 and others obtained in the meanwhile2) by showing that equivalence holds indeed with respect to many-one degrees (but in most cases not m y more for oneone degrees) for all the general decision problems mentioned above and many others as for example decision problems for Tag systems and Markov algorithms. Following that paper [37] up to now there has been a prolific production of proofs of new such equiva.lences including AANDERAA, BELSNES [ [53], SINGLETARY [67]. We want to present here a new approach to such equivalence proofs which permits to unify the myriad individual methods in the literature cited by bringing them back to some few and simple fundamental ideas explicitely formulated in five lemmata.…”
mentioning
confidence: 99%